(untitled) (Experimental biology, 2018)
The development of alternative methods in toxicological testing is relevant for several reasons: a) the ability to test a large number of substances in a relatively short time and under the same conditions; b) the presence of a variety of models in vitro; c) cost-effective for the research by replacing laboratory ani- mals with in vitro models. One of the results of this work is the humanization of toxicological studies by reducing the number of laboratory animals used in the experiment. According to this, the development of a method for assessing the local irritant effect of certain substances that has well-known corrosive ef- fect on the mucous membranes will be useful, especially for substances such as iodine and its complexes with bioorganic ligands. The purpose of this work was to evaluate the possibility of using the MDCK cell line as an in vitro model for studying the irritant effect of new iodine coordinated compounds (CC-143, CC-144, CC-145) using the MTT test. The reference substance was povidone iodine (PVP-iodine), the sodium lauryl sulfate (SLS) was used as a well-studied control substance and recommended for toxicological studies in vitro. It has been shown that PVP-iodine, SLS, CC-143, CC-144 and CC-145 demonstrate classical dose- dependent cytotoxicity against MDCK cell line. The cytotoxic concentration (CC50) for PVP-iodine is significantly lower in comparison with the CC50 for coordinated compounds. Moreover, the cytotoxic effect of CC on MDCK does not depend on the incubation time, from 3 to 72 hours. The practical significance of the work lies in the fact that the MDCK cell line can be offered as an alternative model in screening studies of the local irritant effect of new CС iodine compounds. Key words: alternative method, MDCK, model of epithelial cells in vitro, coordinated compound of iodine.